APPLICATION OF RANGE OF MOTION EXERCISE THERAPY IN PATIENTS EXPERIENCING INEFFECTIVE PERIPHERAL PERFUSION WITH TYPE 2 DIABETES MELLITUS AT PASAR REBO HOSPITAL, JAKARTA: APPLICATION OF RANGE OF MOTION EXERCISE THERAPY IN PATIENTS EXPERIENCING INEFFECTIVE PERIPHERAL PERFUSION WITH TYPE 2 DIABETES MELLITUS AT PASAR REBO HOSPITAL, JAKARTA - Tsania Rachim, Dina; Susanti, Devi; Yohana Wiratikusuma (STIKes Mitra Keluarga, 2024)
Introduction: Health problems can affect the systems in the human body, one of which is the endocrine system, which is often disrupted. Endocrine health problems are diseases that attack the endocrine system. There are many types of diseases that attack the endocrine system, one of which is diabetes mellitus. Objective: To provide an overview of nursing care for patients who has ineffective peripheral perfusion with diabetes mellitus type 2 using the application of range of motion exercise therapy at RSUD Pasar Rebo. Method: Qualitative descriptive research type with a case study research method, namely, by collecting data. Sources of assessment data were obtained from observation, interviews, family, nursing notes and literature study. Results: The results of the research in this scientific paper proposal, based on the results of case studies in several research journals, state that it was found that there was a good influence on the AnkleBrachial Index (ABI) as an indicator of the resolution of the problem of ineffective peripheral perfusion, after carrying out range of motion exercise therapy in patients with diabetes. experiencing ineffective peripheral perfusion problems with diabetes mellitus type 2 with an implementation duration of 2 days. Conclusion: In nonpharmacological therapy by carrying out range of motion exercise therapy, peripheral perfusion problems were not effectively resolved. by the improving of Ankle-Brachial Index value.